В копилку этимологий иранских языков - Эдельман, Д. И. (ИАЭ)
Статья посвящена вопросам изучения истории иранской языковой семьи не только на материале крупных языков с богатой литературной традицией, но и так называемых «малых» языков, включая бесписьменные, и диалектов, хранящих информацию о собственном историческом пути. Автор отмечает ценные свойства научного почерка В. А. Ефимова, его умение сочетать скрупулезность в записи материала живого малого бесписьменного языка с вниманием не только к его современной системе, но и к его глубочайшей истории. Это дает возможность последующим исследователям пользоваться трудами В. А. Ефимова в изучении иранских языков как в синхронно-типологическом аспекте, так и в различных сравнительно- исторических исследованиях. The article is devoted to the study of the history of the Iranian language family, not only through major languages with a rich literary tradition, but also through the so-called “minor” languages, including unwritten ones, and through dialects that store information about their own historical path. The author highlights the distinctive features of the work of Dr. Valentin A. Efimov, his ability to combine scrupulousness in recording the material of a living minor non-written language with attention not only to its present configuration, but also to its deepest history. This has enabled subsequent researchers to benefit from the works of V.A. Efimov in the study of various Iranian languages, both in their synchronous-typological aspect, and in various comparative historical studies.
Keywords: Лексикография